Constructing Brand Credibility Through Influencer Personal Branding on Instagram:A Semiotic and Qualitative Analysis - Joko Suryono; Tsalasa An Nisaa; Bono Setyo; Rosninawati Hussin; Hariyanto Hariyanto (Profetik: Jurnal Komunikasi, 2025)
The rapid growth of social media has transformed advertising strategies, particularly for micro, small, and medium enterprises (MSMEs) seeking to build brand credibility in highly competitive digital environments. As audiences increasingly trust individual figures over corporate messages, influencer-based personal branding has emerged as a strategic form of digital marketing communication. This study aims to analyze how personal branding–based advertising strategies contribute to brand credibility and sales performance, using the Instagram endorsement of the Healthy Water brand by food content creator Rimbang Rayya as a case study. This research employs a qualitative phenomenological approach. Data were collected through in-depth interviews with the influencer, MSME brand owners, and active followers, complemented by Instagram content analysis and participant observation. Data validity was ensured through source and method triangulation. The analysis was guided by Peter Montoya’s Eight Laws of Personal Branding, encompassing specialization, leadership, personality, distinctiveness, visibility, unity, persistence, and goodwill. The findings indicate that Rimbang Rayya’s personal branding is constructed through consistent food-focused content, experiential product engagement, storytelling techniques, and authentic, informative communication. The integration of the eight personal branding elements successfully fosters audience trust, emotional connection, and perceived credibility, which are subsequently transferred to the endorsed brand. This strategy not only enhances the brand image of Healthy Water but also generates measurable outcomes, including increased audience engagement and significant growth in product sales. The study concludes that influencer personal branding functions as a relational and symbolic advertising mechanism capable of converting personal credibility into brand equity for MSMEs. Theoretically, this research extends the application of the Eight Laws of Personal Branding within digital influencer advertising contexts. Practically, it offers a strategic model for MSMEs to develop sustainable, trust-based advertising through authentic personal branding on social media platforms.